Industry space and skill-relatedness of economic activities: Comparative case studies of three eastern German automotive regions - Anne Otto; Antje Weyh (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
The resilience and growth prospects of a region depend crucially on the extent to which industry-specific human capital can be redeployed across the industries of a regional economy. To this end, we present a toolbox to analyse a region's industrial structure, development prospects and economic resilience. With the help of this toolbox human capital similarities, or skill-relatedness, among industries are highlighted. The core of these analyses is the so-called industry space, a network that connects industries with similar human capital requirements. For the time period 1999 to 2008, a regional comparative analysis of three eastern German automobile regions, namely south-west Saxony (SWS), Eisenach region (EIS) and Leipzig region (LEI), is conducted. The objective is to highlight similarities and differences in the composition of the general automobile-oriented knowledge bases between these regions. In addition, the region-specific growth prospects of economic activities, in general and with a closer look at car manufacturers and automotive suppliers, are scrutinized and evaluated in greater detail for each region. This regional comparison is complemented by an investigation of the regional and industrial origins of labour inflows and by a simulation of labour shifts between shrinking and growing industries to figure out as to what extent redundant labour can be reallocated between skillrelated pairs of industries in each region under examination. [...] – – Die Resilienz einer regionalen Ökonomie hängt maßgeblich davon ab, inwiefern relevantes spezifisches Humankapital zwischen deren Wirtschaftsaktivitäten wieder verwertet werden kann. Zu diesem Zweck wird das Instrumentarium Industry Space, das sich auf die Ähnlichkeiten in der Nutzung von Humankapital bzw. Skill-Relatedness zwischen Branchen stützt, zur Beschreibung der Wissensbasis zwischen den vorhandenen Wirtschaftszweigen einer Region sowie zur Analyse von dessen Wachstumsperspektiven und Resilienz vorgestellt. Beim Industry Space handelt es sich um ein Netzwerk von Branchen, die skill-related sind. Das Instrumentartium Industry Space wird im Rahmen von drei vergleichenden Fallstudien der ostdeutschen Automobilregionen Südwestsachsen (SWS), Eisenach (EIS) und Leipzig (LEI) eingesetzt für den Zeitraum 1999 bis 2008. Zum einen wird mit Hilfe des Industry Space die zwischen den regionalen Wirtschaftsaktivitäten vorhandene Wissensbasis in jeder Automobilregion dargestellt. Zum anderen wird die Einbettung der Automobilhersteller und der Automobilzulieferindustrie durch deren skillrelatedness mit anderen Wirtschaftszweigen jeder Regionen detailliert aufgezeigt.
Keywords: 330